2021
DOI: 10.1111/jfd.13505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaccines against pancreas disease in farmed Atlantic salmon

Abstract: Pancreas disease (PD) caused by salmonid alphavirus (SAV) continues to negatively impact salmon farming. To assess the effect on growth and mortality of three vaccines against PD, two controlled field designs were employed: one controlled field study with individual marked fish (PIT tag) assessing three PD vaccines and three controls groups, and a second controlled field study with group marked fish (Maxilla) comparing two PD vaccines against controls. In addition, a descriptive study using whole cages compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
3
7
0
1
Order By: Relevance
“…At 83 dpc, all the immunized groups had experienced significantly greater weight gain than the Saline group in the order group A > group B > group C. No differences were found in weight gain between the groups at 19 dpc which at this time-point corresponded with the weight gain of the non-challenged group in tank 2, and thus supported the notion that different weight gains observed at later time points post challenge were due to variations in the level of protection against PD between the groups. The difference in post-challenge weight gain between groups A and B in this study corresponds with results from a comparative field efficacy study comparing the same vaccines within the same rearing units under normal farming conditions [32] .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…At 83 dpc, all the immunized groups had experienced significantly greater weight gain than the Saline group in the order group A > group B > group C. No differences were found in weight gain between the groups at 19 dpc which at this time-point corresponded with the weight gain of the non-challenged group in tank 2, and thus supported the notion that different weight gains observed at later time points post challenge were due to variations in the level of protection against PD between the groups. The difference in post-challenge weight gain between groups A and B in this study corresponds with results from a comparative field efficacy study comparing the same vaccines within the same rearing units under normal farming conditions [32] .…”
Section: Discussionsupporting
confidence: 77%
“…This correlated with the lower pancreas tissue loss levels at 54 and 83 dpc in the DNAV immunized fish although this was not significantly lower than the second ranked fish in group B. The only efficacy criterium that was not significantly different between the groups was the mortality, however it was quite low, as reported both in earlier SAV cohabitation challenge experiments [ 10 , 15 ] and commercial farming [ 9 , 31 , 32 , 37 ]. In commercial production, the PD vaccines used in this study are normally administered together with multivalent OAVs.…”
Section: Discussionsupporting
confidence: 56%
“…The short temporal period separating the introduction of SAV2a to Rogaland from Møre og Romsdal in late 2019 (Figure 5A) to the identification of SAV2a-SAV3 co-infections in Rogaland in early 2020 indicates that few barriers exist to co-infections arising. This is consistent with a recent study that documented a PD outbreak involving both SAV2 and SAV3, where around 10% of the infections were SAV2-SAV3 co-infections according to PCR [57]. Another study identified SAV co-infections involving other subtype combinations [14].…”
Section: Discussionsupporting
confidence: 92%
“…This disease is caused by salmonid alphavirus (SAV) (Røsaeg et al 2021 ) named salmon pancreas disease virus (PDV) that is closely related to sleeping disease causing virus of rainbow trout (Muktar et al 2016 ).…”
Section: Current Status Of Fish Vaccines and Its Applications-mentioning
confidence: 99%
“…Clynav, a recombinant DNA vaccine that contains puK-SPDV-poly2#1 plasmid which is responsible for coding of several proteins from salmonid alphavirus subtype 3, has been approved in Norway and EU against this disease (Jansen et al 2016 ; Dalmo 2018 ; Aida et al 2021 ). Recently, a study conducted by Røsaeg et al ( 2021 ) reported the efficacy of vaccines against PD in Atlantic salmons. When fish was vaccinated with two different PD vaccines, they showed variations in the efficacy of PD vaccines.…”
Section: Current Status Of Fish Vaccines and Its Applications-mentioning
confidence: 99%